Subsyndromal delirium compared with delirium, dementia, and subjects without delirium or dementia in elderly general hospital admissions and nursing home residents. Issue 1 (1st December 2016) - Sepulveda, Esteban; Leonard, Maeve; Franco, Jose G.; Adamis, Dimitrios; McCarthy, Geraldine; Dunne, Colum; Trzepacz, Paula T.; Gaviria, Ana M.; de Pablo, Joan; Vilella, Elisabet; Meagher, David J.
Abstract: Introduction: Subsyndromal delirium (SSD) complicates diagnosis of delirium and dementia, although there is little research comparing their symptom profiles. Methods: Cross‐sectional study of 400 elderly patients' admission to a general hospital or nursing home diagnosed with delirium, SSD, dementia, or no‐delirium/no‐dementia (NDND). Symptom profiles were assessed using the Delirium Rating Scale‐Revised‐98 (DRS‐R98). Results: Twenty percent patients had delirium, 19.3% had SSD, 29.8% had dementia‐only, and 31% had NDND. Eighty‐one percent of subsyndromal and 76% of delirium groups had comorbid dementia. DRS‐R98 scores showed ascending severity from NDND < dementia‐only < SSD < delirium. DRS‐R98 scores for items evaluating the three core symptom domains (cognitive, higher‐order thinking, and circadian) distinguished SSD from delirium and both from nondelirium groups. DRS‐R98 profiles were essentially the same in delirium and SSD subgroups with or without dementia, although total scale scores were generally higher when in comorbid subgroups. Discussion: SSD shared characteristic core domain symptoms with delirium, which distinguished each from nondelirium groups, although severity was intermediate in the subsyndromal group. Delirium core symptoms overshadowed the dementia phenotype when comorbid. Milder disturbances of delirium core domain symptoms are highly suggestive of SSD.